Osteomalacia and renal failure due to Fanconi syndrome caused by long-term low-dose Adefovir Dipivoxil: a case report - Qian Xiang; Zhiyan Liu; Yanyan Yu; Hanxu Zhang; Qiufen Xie; Guangyan Mu; Jianhua Zhang; Xinan Cen; Yimin Cui (BMC, 2020)
Abstract Background Progressive bone pain and fracture and abnormal positron emission tomography combined with a computed tomography are main reasons for the oncologists suspecting bone tumor. During the patient's medical treatment, the oncologists' unfamiliarity with adverse reactions to anti-HBV drugs were main reason for the long-term exposure to the drug and the adverse reaction (ADR) experienced by the patient. Case presentation A 63-year-old Chinese man had a 27-month history of progressive generalized bone pain combined with spontaneous fractures. Positron emission tomography combined with a computed tomography, revealed an abnormal increase in ribose metabolism and low positron serum inorganic phosphorus concentration (0.7; 0.78-1.65 mmol/L). Serum creatinine level was 252 μmol/L (53-97) μmol/L, and glomerular filtration rate was 22.79 mL/min/1.73 m2. The patient was referred to a multidisciplinary clinic to clarify the diagnosis of myeloma or bone tumor for further treatment in 2017. His medical history revealed that he had a 30-year history of chronic hepatitis B infection. He had received lamivudine at a daily dose of 100 mg for 19 years (1990 to 2009), which had been changed to adefovir (10 mg/day) owing to lamivudine resistance in 2009. Based on the changes in the patient's laboratory markers and the results of emission computed tomography and other radiographic findings, adefovir-induced hypophosphatemic osteomalacia due to acquired renal Fanconi syndrome was suspected by the clinical pharmacist. Considerable clinical improvement was observed after adefovir discontinuation and the administration of entecavir (1.0 mg, every other day). Conclusion Fanconi syndrome with osteomalacia can develop in patients with chronic hepatitis B infection being treated with adefovir at a conventional low dosage of 10 mg/day. This case highlights the importance of ADR as a differential diagnosis and the need of pharmacists with drug safety expertise expert in the patient management.